PENGARUH TREN FOMO TERHADAP MINAT BERJUALAN PELAKU UMKM DI AREA CAR FREE DAY - Muhammad Irham; Nazhifa Zhafira Zea; Winda Safina (Jurnal Genta Mulia, 2026)
The development of social media has given rise to the phenomenon of Fear of Missing Out (FOMO), which refers to the feeling of anxiety about missing information, opportunities, or trends that are currently popular. This phenomenon not only influences consumer behavior but also affects the business decisions of Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the influence of FOMO trends on the selling interest of MSME actors in the Car Free Day (CFD) area. The research employed a descriptive qualitative approach using purposive sampling techniques. The informants consisted of MSME actors who actively sell products in the CFD area and regularly use social media in their daily activities. Data were collected through interviews, observations, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings indicate that social media trends play a significant role in encouraging MSME actors to engage in selling activities at CFD events. Information about viral products, the success of other sellers, and content showcasing potential profits motivate MSME actors to start or expand their businesses. In addition, FOMO encourages MSME actors to respond more quickly to changing trends in order to avoid missing market opportunities. However, decisions to follow trends are also influenced by considerations such as profitability, business capital, and product suitability. The study further reveals that FOMO has both positive and negative impacts. On the positive side, it increases awareness of business opportunities, while on the negative side, it may lead to losses when business actors follow trends without adequate planning and careful consideration.